The Therapeutic Potential of Mesenchymal Stem Cells in the Treatment of Atherosclerosis - Ogay, Vyacheslav; Sekenova, Aliya; Li, Yelena; Issabekova, Assel; Saparov, Arman (Current Stem Cell Research & Therapy, 2021)
Atherosclerosis is a multifactorial and complex disease involving the arterial intima of the circulatory system. The main risk factors of atherosclerosis are diabetes mellitus, hypertension, hyperlipidemic states, smoking, mental stress, unhealthy diet, and a lack of physical activity. Recent studies have shown that dyslipidemia, inflammation and immune cells are involved in all stages of the development of atherosclerosis. Mesenchymal stem cells are a heterogeneous subset of multipotent cells that can be isolated from nearly all human organs and tissues, and they possess both regenerative and immunomodulatory properties. Recent studies have shown that mesenchymal stem cells are able to provide immunosuppressive, regenerative, and atheroprotective effects by reducing dyslipidemia, inflammation and inhibiting endothelial cell dysfunction and plaque formation during the development of atherosclerosis in animal models. Based on these beneficial effects, mesenchymal stem cells are considered a promising alternative therapeutic approach for the effective treatment of atherosclerosis. In this review, we summarize the current findings on potential applications of mesenchymal stem cells for preventing and regressing atherosclerosis as well as discuss strategies for improving the efficacy of mesenchymal stem cell-based therapy.
Keywords: genetic modification